1980
DOI: 10.1007/bf03216548
|View full text |Cite
|
Sign up to set email alerts
|

The anodic behaviour of gold

Abstract: The dissolution of gold in alkaline solutions containing cyanide ions is of great importante and its application in the MacArthur-Forrest process towards the end of the last century revolutionized the extraction of gold from its ores. Because of this, and its use in many industrial processes involving gold, it has been widely studied. What is known-and still unknown-about this reaction constitutes the main theme of this second instalment of a review of the anodic behaviour of gold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 10 publications
(15 reference statements)
4
42
0
1
Order By: Relevance
“…Previously, it has been suggested that this film is some form of gold cyanide, such as AuCN. [28,29,30] The results shown in Figure 8 are consistent with this explanation.…”
Section: Leaching Of Gold In Aerated Cyanide Solutionssupporting
confidence: 93%
See 1 more Smart Citation
“…Previously, it has been suggested that this film is some form of gold cyanide, such as AuCN. [28,29,30] The results shown in Figure 8 are consistent with this explanation.…”
Section: Leaching Of Gold In Aerated Cyanide Solutionssupporting
confidence: 93%
“…It has been shown that deposition of lead onto the gold surface is responsible for the greatly improved oxidation kinetics. [30,[32][33][34] Once the potential exceeds Ϫ200 mV, the oxidation of gold begins to passivate, and at a potential of 0 mV, the current is only slightly higher than that measured in the absence of lead. It has been suggested that the passivation of the gold surface in the presence of lead is a result of the oxidation of lead on the gold surface, rendering it inactive.…”
Section: Leaching Of Gold In Aerated Cyanide Solutionsmentioning
confidence: 55%
“…Evidence of the formation of an oxide layer around this potential is also found in the literature. [22] This can be further illustrated from the Eh-pH diagram for Au-H 2 O, [23] which shows that in alkaline solutions, gold becomes oxidized to Au(OH) 3 at a potential of around 0.9 V at a temperature of 25 ЊC. The relevant equation is…”
Section: ͓ ͔mentioning
confidence: 99%
“…5,7 Other ions in solution can also compete for sites on the gold electrode surface and change the kinetics of the adsorption mechanism. 8 In the reverse case of dissolution, rather than deposition, it has been shown that lead affects the dissolution of gold 2,4 as well as the oxidation. 6 This is postulated to be a surface effect.…”
Section: Introductionmentioning
confidence: 98%
“…1 One is the passivation of gold surfaces, which prevents electrochemical leaching and hence recovery from an ore. 2 The other is the loss of gold from a 'pregnant' (gold-containing) solution and is generally blamed on carbonaceous materials. 2 Lead has been added to the leaching solution to counteract the first problem since about 1930 3 but its effect is not really understood. Jeffrey et al 4 have shown that at low concentrations lead increases the leaching rate but at higher concentrations it passivates the surface and the leaching ceases.…”
Section: Introductionmentioning
confidence: 99%